Effect of Storage Time on DNA Content and Purity in Lip Print - Ahmad Yudianto; Titik Erliyah; Abdul Hadi Furqoni; Indah Nuraini; Qurrota A'yunil Huda (Jurnal Biosains Pascasarjana, 2023)
Forensic experts in uncovering the truth of a case must go through identification, documentation, and collection of evidence. Sometimes at a crime scene, lip prints are found on the surface of an object such as the mouth of a plastic bottle. Lip print research on plastic bottle mouths was carried out for 1, 3 and 7 days. There are 21 samples with details of 3 as controls, 6 samples for the first day, 6 samples for the 3rd day, and 6 samples for the 7th day. DNA extraction using DNAzol, quantification using UV spectrophotometer, and DNA amplification using STR primers, namely TPOX and TH01 loci. For DNA visualization using acrylamide gel. The average results of lip print DNA levels for 1, 3, and 7 days were 369.82 g/ml, 550.72 g/ml, 318.02 g/ml. The average yield of lip print DNA purity for 1, 3, and 7 days was 1.79; 1.78 and 1.79. From the results of DNA quantification, the lowest and highest DNA levels were taken on days 1, 3, and 7. Of the 6 samples and 3 controls amplified using the TPOX and TH01 loci, the results were clearly visible on the acrylamide gel band.